Bounds for Commutators of Multilinear Fractional Integral Operators with Homogeneous Kernels (Analysis in Theory and Applications, 2011)
We will show bounds for commutators of multilinear fractional integral operators with some homogeneous kernels.
Keywords: multilinear operator; fractional integral; commutator; multiple weight; homogeneous kernel.